2023
DOI: 10.1093/geroni/igac079
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Risk Help-Seeking Among Middle- to Old-Age Adults: A Systematic Review

Abstract: Background and Objectives Suicide has become a major public health concern worldwide and in the United States. Rates of suicide increase during the life course and are highest among middle- to old-age adults. Help-seeking represents a crucial coping mechanism that can mitigate suicide risk. Yet, less is known about suicide risk help-seeking, especially among these age groups. To address this knowledge gap, a systematic review of existing literature was performed to obtain a refined understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
2
0
0
Order By: Relevance
“…Despite their elevated depressed mood, only a small proportion of those with PH received any mental health treatment within the preceding 2 months of their death. Our finding is consistent with a recent systematic review that showed low rates of suicide risk help-seeking and service utilization among middle-aged and older adults ( Wang et al, 2023 ). Treatment nonreceipt may have been in part due to unaffordability and other barriers to accessing care (e.g., transportation, provider unavailability, stigma, mistrust of treatment providers; NCIPC, 2021 ; Wang et al, 2023 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite their elevated depressed mood, only a small proportion of those with PH received any mental health treatment within the preceding 2 months of their death. Our finding is consistent with a recent systematic review that showed low rates of suicide risk help-seeking and service utilization among middle-aged and older adults ( Wang et al, 2023 ). Treatment nonreceipt may have been in part due to unaffordability and other barriers to accessing care (e.g., transportation, provider unavailability, stigma, mistrust of treatment providers; NCIPC, 2021 ; Wang et al, 2023 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our finding is consistent with a recent systematic review that showed low rates of suicide risk help-seeking and service utilization among middle-aged and older adults ( Wang et al, 2023 ). Treatment nonreceipt may have been in part due to unaffordability and other barriers to accessing care (e.g., transportation, provider unavailability, stigma, mistrust of treatment providers; NCIPC, 2021 ; Wang et al, 2023 ). Of those who were in treatment, non-adherence to treatment regimen or premature termination may have been a problem ( NCIPC, 2021 ).…”
Section: Discussionsupporting
confidence: 93%